Many Rivers to Cross: Social Identity, Cognition, and Labor Mobility in Rural India. Issue 1 (September 2021) - Michiels, Sébastien; Nordman, Christophe Jalil; Seetahul, Suneha
This study analyzes whether individual skills and personality traits facilitate labor market mobility of disadvantaged groups and rural migrants. We use a panel dataset of individuals in rural South India to explore the relationship between individual cognitive skills, personality traits, and income mobility. We take advantage of intragroup heterogeneity in terms of cognitive skills and personality traits to examine whether these personal characteristics enable individuals to overcome rigid social structures, exploring the role of these skills and traits in migrants' income mobility. We show that despite strong rigidity in the area's labor market structure, personality traits are important determinants of labor mobility, enabling individuals to overcome caste and gender discrimination, but that these personality traits do not contribute to increases in migrants' income mobility.